Sustainable waste trade under WTO law : chances and risks of the legal frameworks' regulation of transboundary movements of wastes - Grosz, Mirina (Nijhoff international trade law series ;, 2011)
Waste tends to be understood as the potentially polluting and unsolicited by-product of our daily lives, a source of risk for the environment and human health. Nonetheless, a transboundary market for wastes as valuable raw materials and second-hand goods has emerged, and states ship wastes to specialised disposal and recycling sites abroad. This book provides a thorough analysis of the Basel Convention and the applicable OECD and EU frameworks of regulation. The author adopts a legal approach that encompasses the environmental, human rights, and WTO law aspects of waste trade. It explores the p.